WAYS OF IMPROVING THE ANALYTICAL TOOLS OF THE MECHANISM OF TAX REGULATION OF UKRAINE - Turyanskyy, Yuriy (Економічний дискурс, 2021)
Introduction. Deviations and imbalances that arise in the process of implementing the planned amounts of tax revenues require the implementation of a number of financial and economic measures through prompt intervention in the process of implementing the revenue side of the budget, ie tax regulation. Ensuring stabilization of the country’s development is possible under the condition of reforming tax regulation, the priorities of which are de-shadowing of the economy, reducing the number of taxes and fees and creating incentives for small and medium business development, which actualizes the scientific search Methods. Systemic, institutional methods (for the study of the tax system of Ukraine and mechanisms for regulating tax relations), the method of trend analysis (for the analysis of the dynamics of the tax burden on consumption, the analysis of tax coefficients of direct and indirect taxes) are used. Eurostat data on the main tax aggregates of national accounts of different countries, statistical and analytical information of the State Tax Service of Ukraine, the State Statistics Service of Ukraine, the Ministry of Finance of Ukraine were used as an information source. Results. The task of tax regulation is to regulate supply and demand with the help of direct and indirect taxes, the formation of analytical tools for the mechanism of tax incentives for economic activity. Analytical tools of the tax regulation mechanism are proposed to be supplemented by monitoring the parameters of the tax burden in general and in terms of tax efficiency of direct and indirect taxes; econometric models for forecasting the level and impact of the tax burden on the macro parameters of economic stabilization. Their introduction will make it possible to more accurately identify areas for reforming the tax system to improve the efficiency of tax regulation. Discussion. In further research, it is advisable to substantiate the priority areas of reforming the tax system of Ukraine to stabilize economic processes and develop practical recommendations for improving tax instruments.